Reimagining Student Success through Engagement and Soft Outcomes: Learning from a Capstone Course in a Canadian Polytechnic - Mulcahy, Clare; Khan, Mohammad Ashiqur Rahman (Teaching and Learning Inquiry, 2025)
This paper uses a capstone class in the bachelor of technology program at Northern Alberta Institute of Technology (Canada) as a case study for reimagining a “successful” student and promoting growth in a variety of learners. In this course, students, guided by faculty advisors, work in teams to address real-world projects solicited by individuals or organizations. Over two years, feedback was gathered through interviews and surveys with graduating students and alumni to identify opportunities for improvement and to gain deeper insight into students’ learning experiences. The authors analyze these responses through the lens of scholarship of teaching and learning (SoTL), particularly through literature on soft outcomes. In comparison to hard outcomes like grades or completing a degree, soft outcomes capture student advancement toward the goals of a particular course and can include interpersonal, organizational, and internal development. Ultimately, we conclude that our course promotes students’ progress toward soft outcomes through their relationships with their project sponsors, instructors, and teammates. Our findings emphasize the importance of fostering students’ social, emotional, and personal growth and suggest that the students who might be perceived as low-achieving can still advance as much on their learning journey as the ones who would be traditionally lauded as high-achieving. We align our findings with scholarship that investigates students’ emotional growth and wellbeing, which can be difficult amidst pedagogy, research, and government policy that define the value of post-secondary education primarily in terms of its ability to prepare students for the job market. This paper reframes what being a successful student means, contributes to a wider body of research on soft outcomes, and provides valuable insight for educators and researchers who are invested in students’ engagement.